2016
DOI: 10.1002/admt.201600144
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Contained Handheld Magnetic Platform for Point of Care Cytometry in Biological Samples

Abstract: Magnetic levitation is a powerful tool capable of distinguishing micrometerscale particles based on their densities. When a particle is suspended in a paramagnetic medium and placed in a magnetic field formed by two permanent magnets with like poles facing each other, the particle will experience two forces-a magnetic force and a buoyant force. These forces cause a particle, such as a cell, which does not necessarily have magnetic properties, to levitate at a height inversely proportional to its density. Magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 31 publications
0
47
0
2
Order By: Relevance
“…Insbesondere die Demirci‐Gruppe hat innovative Beiträge zur Trennung, Analyse und Selbstorganisation biologischer Zellen (insbesondere Einzelzellenanalyse) geleistet . Ghiran, Tasoglu und Kollegen haben eine Reihe neuer Techniken (insbesondere beim kombinierten Einsatz von MagLev und Smartphones) und Anwendungen in der medizinischen Analyse (Zellen und Assays) entwickelt . Die Yildiz‐Gruppe hat eine Methode zur Durchführung gerüstfreier Zellkulturen entwickelt .…”
Section: Einführungunclassified
See 1 more Smart Citation
“…Insbesondere die Demirci‐Gruppe hat innovative Beiträge zur Trennung, Analyse und Selbstorganisation biologischer Zellen (insbesondere Einzelzellenanalyse) geleistet . Ghiran, Tasoglu und Kollegen haben eine Reihe neuer Techniken (insbesondere beim kombinierten Einsatz von MagLev und Smartphones) und Anwendungen in der medizinischen Analyse (Zellen und Assays) entwickelt . Die Yildiz‐Gruppe hat eine Methode zur Durchführung gerüstfreier Zellkulturen entwickelt .…”
Section: Einführungunclassified
“…Demirci, Ghiran, Tasoglu, Arslan‐Yildiz und Mitarbeiter haben MagLev um dichtebasierte Analysen und Trennungen einzelner Zellen erweitert, einschließlich der Entwicklung eines diagnostischen Prototyps zur Diagnose von Sichelzellkrankheiten (Abbildung F) . Tabelle fasst die Anwendungen von MagLev zur Analyse, Trennung, und Manipulation von Zellen (von Bakterien und Hefezellen bis hin zu Säugetierzellen und ganzen Organismen) zusammen.…”
Section: Anwendungenunclassified
“…This technology has been applied in numerous fields, representing the large variety of possible applications, including the consumer goods industry [1] , aerospace research [2,3] , regenerative medicine [4][5][6][7][8][9][10][11][12] , medical device development [13][14][15][16][17][18][19] and the automotive industry [20] . An emerging application of 3D printing is for drug manufacturing [21,22] .…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that specific diseases show characteristic changes in density for particular types of cells. Tasoglu and co‐workers reported a portable and self‐contained device offering a great potential for rapid and on site sample analysis such as white blood cell cytometry . Their point‐of‐care Maglev device was able to perform cell cytometry of a particular population of cells (i.e., white blood cells) from a mixed population in human blood.…”
mentioning
confidence: 99%
“…Tasoglu and co-workers reported a portable and self-contained device offering a great potential for rapid and on site sample analysis such as white blood cell cytometry. [4] Their point-of-care Maglev device was able to perform cell cytometry of a particular population of cells (i.e., white blood cells) from a mixed population in human blood. They have also combined Maglev technique with fluorescence imaging to provide specific clinical assays.…”
mentioning
confidence: 99%